Smartphones usage among undergraduates of university of ibadan: an implication for academic learning (2015)
There is a new revolution regarding the use of information communication technologies (ICTs) among undergraduate students in Nigeria with regard to smartphones application to academic learning. Colligan (2012), in a survey on smartphones users reported that some youths spend close to 6 hours or more on their phone in one day. Hence, to what extent could smartphones contribute to students ’ academic learning. This study used the qualitative and quantitative methods of research with the questionnaire and focus group discussion guides as instruments to gather relevant information for the study. Five hundred (500) male and female undergraduate students from various departments in the University of Ibadan who are smartphones users were selected for the survey questionnaire while Focus Group Discussion sessions were held with selected students on their perception of smartphones usage as a learning device among students in the university community. Findings reveal that majority of the students reported frequent use of applications such as Dictionary (91%), Face book (88.6%), 2go (88%), Twitter (82%), YouTube (78.8%), Whatsapp (60.4) and Linkedln (54.6%) on their smartphones device. Findings also show that an appreciable proportion of the respondents (22.2%) spend 1 hour a day on reading/downloading academic applications like PDF articles/journals on smartphones. Students reported the usage of smartphones for academic purpose with 91% stating that the use of smartphones has reduced their dependency on computer-based learning and 83% use their smartphones to look up words in the dictionary application. Further findings from the t-test reveal a significant influence of gender on smartphones use among students (p<0.01). Though the female students were reported as using more smartphones than their male counterpart (t (498) = -9.62, p<01), more male students use academic-oriented applications on their smartphones than their female counterpart whose use are more for socializing. This study has established that the smartphone is a useful device that can enhance academic learning among undergraduate students hence it should be encouraged in order to promote new dimension of information communication technologies (ICTs) in the emerging generation of educational development in developing countries.